2006
DOI: 10.1111/j.1440-1681.2006.04432.x
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH INHIBITION OF MESENCHYMAL STEM CELLS BY ASPIRIN: INVOLVEMENT OF THE WNT/β‐CATENIN SIGNAL PATHWAY

Abstract: 1. Mesenchymal stem cell (MSC) therapy is drawing increasing attention in cardiology. However, the effect of aspirin, an assistant medication used extensively in the treatment of cardiovascular diseases, on MSC is not clear. 2. In the present study, we investigated the effect of aspirin on the growth of MSC in vitro and the underlying mechanism of its action. 3. The 3-(4,5-dimethyl-2 thiazoyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay revealed that 1, 5 and 10 mmol/L aspirin inhibited the growth of MSC b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 44 publications
6
33
0
Order By: Relevance
“…Therefore, we observed the changes in levels of Bcl2, BAX, and cleaved caspase-3 in rat TSCs and determined that aspirin-induced apoptosis occurs through the mitochondrial/ caspase-3 pathway. Our results from this study are similar to those found in previous research [32][33][34][35]. We confirmed our results using an immunofluorescence assay in rat Achilles tendons.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, we observed the changes in levels of Bcl2, BAX, and cleaved caspase-3 in rat TSCs and determined that aspirin-induced apoptosis occurs through the mitochondrial/ caspase-3 pathway. Our results from this study are similar to those found in previous research [32][33][34][35]. We confirmed our results using an immunofluorescence assay in rat Achilles tendons.…”
Section: Discussionsupporting
confidence: 83%
“…Li et al revealed that the canonical Wnt/β-catenin pathway inhibits the apoptosis of tumor cells and mesenchymal stem cells [40] and modulates the differentiation of stem cells [31][32]. Therefore, we next investigated the role of the canonical Wnt/β-catenin pathway in aspirin-induced TSC apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A strong cytotoxic effect of tolfenamic acid on canine and equine stem cells was recorded in the first and last day of the culture, when cell death was detected. This finding is partially consistent with the previous study performed by Wang et al (2006), where the highest concentrations of aspirin added to the medium were effective in inhibiting the growth of MSCs, without concomitant increase in cell death. It can be assumed that the different values of proliferation observed in our study in ASCs isolated from various species may be due to the different mechanisms of drug metabolism pathways in canine and equine stem cells.…”
Section: Discussionsupporting
confidence: 83%
“…therapy used in interventional procedures but include oral medications that are widely used in primary and secondary prevention. For example, a 1-10 mmol·L -1 dose of aspirin has been shown to inhibit proliferation of mesenchymal stem cells (MSCs) in rats through a mechanism of action thought to involve inhibition of PGE2 formation and subsequent down-regulation of the Wnt/b-catenin signalling pathway (Wang et al, 2006). Treatment of MSCs with PGE2 increases cell proliferation and enhances the activation of the Wnt/bcatenin pathway (Kleiveland et al, 2008).…”
Section: Figurementioning
confidence: 99%